Wearable sweat sensing for prolonged, semicontinuous, and nonobtrusive health monitoring. Issue 4 (15th October 2020) - Moonen, Emma J.M.; Haakma, Jelte R.; Peri, Elisabetta; Pelssers, Eduard; Mischi, Massimo; den Toonder, Jaap M.J.
Abstract: Together with the upcoming market for wearable consumer technologies, noninvasive and continuous health monitoring has become a new trend in the healthcare landscape. In recent years, significant research has been targeted toward the development of wearable sensing devices for monitoring biomarker levels in nonobtrusively accessible biofluids such as tears, urine, saliva, and sweat. Sweat could be an ideal candidate for prolonged, semicontinuous, and nonobtrusive health monitoring because sweat is a continuously accessible biofluid containing physiologically and metabolically rich information. However, challenges still remain toward commercialized wearable sweat‐sensing devices, and the correlation between biomarker concentrations in sweat with health conditions still seems to be not fully understood. This review article aims to display the full scope of sweat sensing for health monitoring, starting from the fundamentals of human sweat, via modeling of the sweat gland physiology toward wearable sweat‐sensing devices in research and commercialization efforts. Finally, the challenges of sweat sensing that still have to be overcome toward the utilization of sweat sensing in the conventional healthcare settings are discussed. Abstract : Sweat is an ideal body fluid for prolonged, semicontinuous, and nonobtrusive health monitoring because sweat is a continuously accessible biofluid containing physiologically and metabolically rich information. This review article aims to display the full scope of sweat sensing for health monitoring, starting from the fundamentals of human sweat, via modeling of the sweat gland physiology toward wearable sweat‐sensing devices in research and commercialization efforts.